2007
DOI: 10.1038/nri1984
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of immune tolerance by anti-inflammatory neuropeptides

Abstract: The induction of antigen-specific tolerance is essential to maintain immune homeostasis, control autoreactive T cells, prevent the onset of autoimmune diseases and achieve tolerance of transplants. Inflammation is a necessary process for eliminating pathogens, but can lead to serious deleterious effects in the host if left unchecked. Identifying the endogenous factors that control immune tolerance and inflammation is a key goal in the field of immunology. In the last decade, various neuropeptides that are prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
208
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(230 citation statements)
references
References 103 publications
13
208
1
2
Order By: Relevance
“…A novel approach to drug discovery, based on the study of the body's own natural resolution mechanisms, is currently emerging and finding acceptance in the scientific community 27,28 : MC analogues would fit into this novel category. So far, most efforts have been devoted to the development of MC 4 agonists with potential use in obesity and sexual dysfunction, and there have been a few attempts to exploit the potential use of MC compounds as anti-inflammatory drugs. One reason behind this lack of development could be identification of the MC receptor to be targeted to elicit the desired anti-inflammatory effects, with studies pointing to each of MC 1 , 29 MC 3 , 10 and, more recently, MC 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel approach to drug discovery, based on the study of the body's own natural resolution mechanisms, is currently emerging and finding acceptance in the scientific community 27,28 : MC analogues would fit into this novel category. So far, most efforts have been devoted to the development of MC 4 agonists with potential use in obesity and sexual dysfunction, and there have been a few attempts to exploit the potential use of MC compounds as anti-inflammatory drugs. One reason behind this lack of development could be identification of the MC receptor to be targeted to elicit the desired anti-inflammatory effects, with studies pointing to each of MC 1 , 29 MC 3 , 10 and, more recently, MC 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained in the in vitro MC receptor functional assays revealed that AP214 is a full pan MC receptor agonist (ie, a full agonist against MC 1 , MC 3 , MC 4 , and MC 5 ) and, similar to many other MCs, lacks agonist activity against MC 2 ( Table 1).…”
Section: Ap214 Is a Pan Agonist At Human MC Receptorsmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, CTLA-4 increases T cell motility and overrides TCR induced stop signals required for stable conjugate formation between T cells and antigen presenting cells (APC) [7]. Critical importance of cAMP/protein kinase A (PKA) pathway for regulation of immune tolerance [8] is further supported by inability to develop T and B lymphocytes in mice conditionally deficient in PKA-RIa subunit (Dr. Hua Gu, Columbia University, personal communication). Moreover, overexpression of a newly established marker of T R cells termed G protein-coupled receptor (GPR) 83, inducible by cAMP in naive CD4 + CD25 -T cells, leads to the induction of regulatory Foxp3 + T cells in vivo [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to identify such factors, many researchers have concentrated on traditional immunosuppressive cytokines, such as IL-10 and transforming growth factor-β1 (TGFβ1) [94]. Meanwhile, others have focused their search on neuropeptides and hormones, classically considered as neuroendocrine mediators, but which are also produced by immune cells, especially under inflammatory conditions [47]. …”
mentioning
confidence: 99%